Tinjauan Literatur terhadap Metode Sistem Rekomendasi pada Pasar Online - Rama Dian Syah; Ahmad Hidayat (Jurnal Informatika Universitas Pamulang, 2023)
Product Recommendations for e-commerce activities in online market are important in product promotion to buyers. The Recommendation System in e-commerce can take advantage of growing data to inform the best product recommendations for buyers. Recommendation systems provide great opportunities for businesses so that research on the development of Recommendation System methods is increasing nowadays. This study examines the development of the Recommendation System of e-commerce activities in online market. The purpose of this research is to see a comparison and summary of several studies that have been done. Comparisons and summaries of previous research produce an analysis of research progress and find out problems with the Recommendation System of ecommerce activities in online market. The results of this study provide insight for researchers about the development of research on Recommendation Systems of ecommerce activities in online market.